Natural Products: A Potential Source of Malaria Transmission Blocking Drugs? - Mugumbate, Grace; Moyo, Phanankosi; Elof, Jacobus N.; Louw, Abraham I.; Maharaj, Vinesh J.; Birkholtz, Lyn-Marié (Multidisciplinary Digital Publishing Institute, 2022)
The ability to block human-to-mosquito and mosquito-to-human transmission ofPlasmodiumparasites is fundamental to accomplish the ambitious goal of malaria elimination. The WHO currentlyrecommends only primaquine as a transmission-blocking drug but its use is severely restrictedby toxicity in some populations. New, safe and clinically effective transmission-blocking drugstherefore need to be discovered. While natural products have been extensively investigated for thedevelopment of chemotherapeutic antimalarial agents, their potential use as transmission-blockingdrugs is comparatively poorly explored. Here, we provide a comprehensive summary of the activitiesof natural products (and their derivatives) of plant and microbial origins against sexual stages ofPlasmodiumparasites and theAnophelesmosquito vector. We identify the prevailing challenges andopportunities and suggest how these can be mitigated and/or exploited in an endeavor to expeditetransmission-blocking drug discovery efforts from natural products.